2021
DOI: 10.1111/1467-9817.12372
|View full text |Cite
|
Sign up to set email alerts
|

Stop multitasking and just read: meta‐analyses of multitasking's effects on reading performance and reading time

Abstract: Background Multitasking while reading is a commonplace activity. Many studies have been conducted examining the effect of multitasking on reading comprehension and times. The purpose of this meta‐analysis is to consolidate the empirical findings on reading comprehension and times in order to understand the overall effect of multitasking on reading. Characteristics of the reading situation, comprehension assessment and the secondary task were examined to determine if they varied the effect of multitasking. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…This situation did not allow participants to reread the text after the interruption, especially when the pace was too fast for them. Such an experimental design could explain the decrease in performance ( Oulasvirta and Saariluoma, 2006 ; Bowman et al, 2010 ; Cane et al, 2012 ; Chevet et al, 2021 ; Clinton-Lisell, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This situation did not allow participants to reread the text after the interruption, especially when the pace was too fast for them. Such an experimental design could explain the decrease in performance ( Oulasvirta and Saariluoma, 2006 ; Bowman et al, 2010 ; Cane et al, 2012 ; Chevet et al, 2021 ; Clinton-Lisell, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also notable what is absent from Students’ accounts. For example, there is no awareness of an increased fragmentation of attention caused by multitasking in the digital space, documented in studies of online learning ( Ettinger and Cohen, 2020 ; Bruineberg and Fabry, 2021 ; Clinton-Lisell, 2021 ). Students do not register the abundance of digital stimuli as a loss of an opportunity for focus.…”
Section: Discussionmentioning
confidence: 99%
“…There is some previous evidence of significantly greater self-reported multitasking among users of e-texts versus print books (Daniel & Woody, 2013), though interestingly a recent meta-analysis indicates that multitasking actually has a greater negative effect on student comprehension when reading print sources versus on a screen (Clinton-Lisell, 2021). In our study, we found that self-reported multitasking did not significantly differ between the three modality conditions.…”
Section: Discussionmentioning
confidence: 99%